The initial - Final mass relation for close low- and intermediate-mass binaries - Han, Z; Tout, C; Eggleton, P (2001)
Using Eggleton's stellar evolution code, we carry out 150 runs of Pop 1 binary evolution calculations with initial primary mass between 1 and 8M(circle dot), the initial mass ratio q = M-1/M-2 between 1.1 and 4, and the onset of Roche lobe overflow (RLOF) at an early, middle, or late phase in the Hertzsprung gap. We assume that the RLOF is conservative in the calculations and find that the remnant mass of the primary may change by more than 40 per cent over the range of initial mass ratio or orbital period for a given primary mass. This is contrary to the often held belief that the remnant mass depends only on the progenitor mass if mass transfer begins in the Hertzsprung gap. We fit a formula, with an error less than 3.6 per cent, for remnant (i.e., white dwarf) mass as a function of the initial mass M-li of the primary, the initial mass ratio q(i), and the radius of the primary at the onset of RLOF. We also find that a carbon-oxygen white dwarf with mass as low as 0.33M(circle dot) may be formed if the primary's initial mass is around 2.5M(circle dot).